2019
DOI: 10.1097/ajp.0000000000000681
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Local Anesthetic Versus Botulinum Toxin-A Injections for Myofascial Pain Disorders

Abstract: Objective: Myofascial pain is a chronic pain disorder characterized by the presence of painful localized regions of stiff muscle and/or myofascial trigger points. Intramuscular myofascial trigger point injections are considered first-line treatments for myofascial pain. Common injectates include local anesthetics and botulinum toxin-A (BTX-A). The objective of this systematic review was to compare the effectiveness of local anesthetics and BTX-A on pain intensity in patients with myofascial pain. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 59 publications
1
17
0
4
Order By: Relevance
“…Продолжительность периода ремиссии после инъекций в триггерные точки, достигнутая в данном исследовании, согласуется со сведениями об эффективности инъекционных методик в триггерные точки у пациентов с МБС лица, представленными в специальной литературе [14,16].…”
Section: Discussionunclassified
“…Продолжительность периода ремиссии после инъекций в триггерные точки, достигнутая в данном исследовании, согласуется со сведениями об эффективности инъекционных методик в триггерные точки у пациентов с МБС лица, представленными в специальной литературе [14,16].…”
Section: Discussionunclassified
“…34 However, in randomized controlled double-blind studies comparing BoNT to placebo, local anesthetics, and steroids, there were no significant differences in pain scores. 35,36 The majority of studies have been landmark based or used the site of maximal tenderness as guidance for injections, but there is some evidence that targeted injections focusing on specific muscle groups may improve benefit. 5 This usually requires the use of imaging for guidance.…”
Section: Lateral Epicondylitismentioning
confidence: 99%
“…However, their meta-analysis included stroke patients with hemiplegic shoulders, so the results might not be well-representative of the general population. Conversely, Ahmed et al demonstrated that the local anesthetic injections were more effective than BoNT injections [11]. Nevertheless, their patients had heterogeneous symptoms and some of them presented with myofascial pain over all body regions.…”
Section: Introductionmentioning
confidence: 96%
“…In recent years, BoNT injections have been increasingly used to treat mild musculoskeletal disorders, like tennis elbow, knee osteoarthritis, and refractory joint pain [8][9][10]. However, its effects remain inconclusive regarding chronic shoulder pain based on available systemic reviews and meta-analyses [11,12]. Wu et al concluded that BoNT injections were effective in treating shoulder pain compared with placebo injections [12].…”
Section: Introductionmentioning
confidence: 99%